Pneumatology in the digital age: Reimagining the Holy Spirit’s role in Trinitarian theology - Rendani C. Nthakheni; Ndidzulafhi Mudau (African Journal of Pentecostal Studies, 2025)
Background: The Holy Spirit is becoming increasingly marginalised in contemporary Christian theology and practice, particularly as churches grapple with the technological and philosophical implications of the Fourth Industrial Revolution (4IR).